Common Metabolic Pathways Implicated in Resistance to Chemotherapy Point to a Key Mitochondrial Role in Breast Cancer - Abad, Etna; García-Mayea, Yoelsis; Mir, Cristina; Sebastian, David; Zorzano, Antonio; Potesil, David; Zdrahal, Zbynek; Lyakhovich, Alex; Lleonart, Matilde E (Molecular & cellular proteomics, 2019)
Cancer cells are known to reprogram their metabolism to adapt to adverse conditions dictated by tumor growth and microenvironment. A subtype of cancer cells with stem-like properties, known as cancer stem cells (CSC), is thought to be responsible for tumor recurrence. In this study, we demonstrated that CSC and chemoresistant cells derived from triple negative breast cancer cells display an enrichment of up- and downregulated proteins from metabolic pathways that suggests their dependence on mitochondria for survival. Here, we selected antibiotics, in particular - linezolid, inhibiting translation of mitoribosomes and inducing mitochondrial dysfunction. We provided the first in vivo evidence demonstrating that linezolid suppressed tumor growth rate, accompanied by increased autophagy. In addition, our results revealed that bactericidal antibiotics used in combination with autophagy blocker decrease tumor growth. This study puts mitochondria in a spotlight for cancer therapy and places antibiotics as effective agents for eliminating CSC and resistant cells.
Keywords: transplantace nádorů; Gene Expression Regulation, Neoplastic; nádorové mikroprostředí; Mitochondria; viabilita buněk; Linezolid; Neoplastic Stem Cells; Cell Line, Tumor; Clinical Proteomics; Cell Proliferation; Cancer Stem Cells; Neoplasm Transplantation; regulace genové exprese u nádorů; chemorezistence; Cell Survival; NMR; Breast Cancer; Triple Negative Breast Neoplasms; Chemoresistance; triple-negativní karcinom prsu; Stem Cells; Animals; Autophagy; lidé; Mitochondria Function or Biology; ženské pohlaví; Humans; zvířata; metabolické sítě a dráhy; Antibiotics; myši; proliferace buněk; linezolid; Drug Resistance, Neoplasm; nádorové kmenové buňky; nádorové buněčné linie; Mice; Female; Tumor Microenvironment; Cancer Biology; Metabolic Networks and Pathways; mitochondrie; NMR-metabolomic